Retrospective analysis of fever and sepsis patients from Cambodia reveals serological evidence of melioidosis - Vichaya Suttisunhakul (2019)
© 2018 by The American Society of Tropical Medicine and Hygiene. Burkholderia pseudomallei, the etiologic agent of melioidosis, is predicted to be ubiquitous in tropical regions of the world with areas of highest endemicity throughout Southeast Asia (SEA). Nevertheless, the distribution of B. pseudomallei and the burden of melioidosis in many SEA countries remain unclear. In Cambodia, only two human endemic cases of melioidosis were reported through 2008 and since then only a few hundred cases have been described in the literature. This is in sharp contrast to the annual burden of thousands of cases in surrounding areas. To further investigate the prevalence of melioidosis in Cambodia, we used a recently developed O-polysaccharide-based rapid enzyme-linked immunosorbent assay to detect B. pseudomallei-specific antibodies in serum samples obtained from 1,316 febrile illness or sepsis patients from 10 different provinces. Based on a cutoff value derived through cultureconfirmed melioidosis cases, the proportion of positive samples in our cohort was approximately 12%. Regression analysis indicated that the odds of obtaining a positive result were 2.2 times higher for males than females controlling for age and province (95% confidence interval: 1.6-3.2,P< 0.001). Consistent with this, 9.2% of females were positive versus 18.2% of males (P < 0.001). Notably, 22.5% of grain or rice farmers were positive versus 10.1% of subjects with occupations not involving regular contact with soil. Positive results varied significantly by province. Collectively, the results of this study suggest that the true burden of melioidosis in Cambodia is greater than has previously been reported.